1979
DOI: 10.1111/j.1365-2621.1979.tb06446.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Gelatinization Rate of Rice and Potato Starches

Abstract: The gelatinization rate of rice and potato starches were investigated. The rheological method, using a capillary tube viscometer, was applied for the measurement of the gelatinization degree. The gelatinization rates were measured for the rice and potato starches at temperature ranges of 70-85 and 60~63°C respectively. The rate parameter in the rate equation was given as the Arrhenius equation. The equivalent values of the activation energy for the rice and potato starches were about 14 and 230 k&/g-mol respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
2

Year Published

1986
1986
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(42 citation statements)
references
References 3 publications
5
35
2
Order By: Relevance
“…By a cook time of 3 mins, the data for the 75°C cook temperature had reached a constant viscosity. This is consistent with the observations of Kubota et al (1979), Bakshi and Singh (1980), Lund and Wirakaratakusumah, (1984), Burros et al (1987), andDolan et al (1989). Loading difficulties precluded the cooking of samples for periods of less than one minute.…”
Section: Matefuals and Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…By a cook time of 3 mins, the data for the 75°C cook temperature had reached a constant viscosity. This is consistent with the observations of Kubota et al (1979), Bakshi and Singh (1980), Lund and Wirakaratakusumah, (1984), Burros et al (1987), andDolan et al (1989). Loading difficulties precluded the cooking of samples for periods of less than one minute.…”
Section: Matefuals and Methodssupporting
confidence: 92%
“…Burros et al (1987) used DSC to measure gelatinization of corn meal under low moisture (25%) and high temperature (80-140°C) conditions. They found results similar to those of Kubota et al (1979). Dolan et al (1989), working with high moisture systems (about 90%), found that viscosities at different time-temperature histories could be normalized by (4) It is important to note that, for corn starch, the infinite and initial viscosities are specific to the cook temperature after either correction or normalization to the same temperature.…”
Section: Introductionmentioning
confidence: 56%
“…This result is different even qualitatively from that known for the ordinary case, i.e. the thermal gelatinization of rice starch in a neutral pure water (Kubota et al, 1979).…”
Section: Time Dependence: Newtonian Analysiscontrasting
confidence: 95%
“…(4.118)), in which the activation energy is proven to be a function of concentration and type of starch. The exponent n iil almost independent of temperature [639][640][641], and decreases with increasing gum concentration [639,642].…”
Section: Polymer Matricesmentioning
confidence: 99%